Parametric instability of a submerged floating pipeline between two floating structures under combined vortex excitations. (September 2016) - Wang, Zhiqian; Yang, Hezhen
Highlights: To investigate parametric instability of a submerged floating pipeline combined parametric and vortex excitations. Wake oscillator model is coupled to simulate the lock-in phenomenon considering parametric excitation. Motion of the floating structures is combined to calculate the parametric excitation. The vibration mode jump phenomenon is found during parametric instability analysis. Abstract: This study investigates a parametric instability prediction of a submerged floating pipeline connected between two floating structures under combined vortex excitations. The submerged floating pipeline is considered as a potential solution for fluid transportation between floaters in deepwater. However, the parametric instability combined with vortex-induced vibration is a major concern for its safety. The instability can lead to huge displacement and fatigue damage. Thus, it is essential to propose a methodology for analyzing nonlinear dynamic properties of the pipeline with combined parametric and vortex excitations. Here, coupled vibration equations of the pipeline are established, including hydrodynamic force model which contains vortex-induced load and structural model which contains parametric excitation due to motion of the two floating structures. Then Mathieu equation is derived from the homogeneous structural equation. Differences between the dynamic responses subjected to only vortex excitation and combined excitations are compared. The pipeline engineering cases and the effects of two important design factors are analyzed. The results show that the parametric instability may occur in cross-line vibration of the submerged floating pipeline between the two floaters. Even the maximum vibration amplitude of the pipeline under combined excitations is still larger than that under only vortex excitation, when the parametric instability does not take place. There is a vibration mode jump phenomenon while the parametric instability occurs. In addition, two design factors, transfer coefficient and phase angle of the floaters' motion, can make a great impact on the parametric stability of the submerged floating pipeline.